Hands-on machine learning with Microsoft Excel 2019 : build complete data analysis flows, from data collection to visualization - Martino, Julio Cesar Rodriguez (Packt Publishing, 2019)
Machine learning has become a core necessity for every business and organization. With this book, you will learn to analyze your Excel data to search for patterns and return a series of interesting facts or trends about the data. You will learn to perform machine learning tasks using Excel plugins and APIs without much code required.